Menguak Realitas Jejak “Goah” Sebagai Simbol Sakralitas Pertanian Di Desa Ciasmara Kecamatan Pamijahan Kabupaten Bogor - Supriatna, Raden Atang; Nugraha, Yogaprasta Adi (Lembaga Penelitian Dan Pengabdian Kepada Masyarakat Universitas 17 Agustus 1945 Surabaya, 2022)
Agriculture is one of the important sectors that contribute to national income. However, agricultural development currently has a tendency to increase productivity so that it impacts on the agricultural system which tends to make agriculture is more just an activity that produces agricultural